Una educación estadística: para una sociedad que tolere la incertidumbre - Rocha Salamanca, Pedro (Revista Científica, 2011)
This paper is both a review of the background and part of the framework for the thesis: “Classroom practices of the Statistics teachers of the college of engineering faculty” It’s perspective shows statistics as a key element in decision making, when humans face uncertain situations.